1987
DOI: 10.1007/bf00330443
|View full text |Cite
|
Sign up to set email alerts
|

Gene cluster for streptomycin biosynthesis in Streptomyces griseus: Analysis of a central region including the major resistance gene

Abstract: A central segment of a cluster of biosynthetic genes for the antibiotic streptomycin cloned from Streptomyces griseus was analysed for open reading frames, as well as for transcriptional and translational activity. The nucleotide sequence revealed two significant open reading frames, ORF1 and APH(6), orientated in opposite directions and with a spacer of 885 bp between the start codons. The first, ORF1, had a coding capacity of 38 kDa. One open reading frame, APH(6), was identified as the major resistance gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…A partial streptomycin biosynthetic gene cluster was then identified in 1987. 13 Subsequently, several biosynthetic genes for streptomycin were identified in association with the central gene cluster. 14 However, only a few biosynthetic genes were heterologously expressed and investigated to characterize the function to date.…”
Section: Introductionmentioning
confidence: 99%
“…A partial streptomycin biosynthetic gene cluster was then identified in 1987. 13 Subsequently, several biosynthetic genes for streptomycin were identified in association with the central gene cluster. 14 However, only a few biosynthetic genes were heterologously expressed and investigated to characterize the function to date.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a variety of promoters sharing little or no sequence resemblance with other bacterial promoters have been found (3,10,17), which suggests that special sigma factors of the Streptomyces RNA polymerase may be involved in transcription (31). Moreover, the genes encoding antibiotic resistances in drug-producing organisms may be linked to the genes involved in antibiotic biosynthesis (9,18) and thus could be used as probes to isolate the biosynthetic pathways of secondary metabolites.…”
mentioning
confidence: 99%
“…Recent studies on the organization of the structural genes for the enzymes involved in antibiotic biosynthesis in the genus Streptomyces revealed that these genes are clustered (4). In the case of peptide antibiotics produced by bacteria of the genus Bacillus, the organization of the genes for the peptide antibiotic synthetases is not yet clarified, because until now genes for only one component enzyme of the multicomponent synthetases have been cloned.…”
Section: Discussionmentioning
confidence: 99%